2008
DOI: 10.1002/pits.20316
|View full text |Cite
|
Sign up to set email alerts
|

Do PDAs enhance the organization and memory skills of students with cognitive disabilities?

Abstract: The project studied the on-time behavior of 35 students with intellectual disabilities (ID) or traumatic brain injury (TBI) under three conditions -times and tasks list, paper planner, and two different personal data assistants (PDAs). Students participated for two 4-week periods, receiving one morning reminder during Period 1 and no reminders during Period 2. Students were on time more often using a PDA compared to a list (p < .024) or a planner (p < .002). Students were on time 50% more often in Period 1 wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 31 publications
0
21
0
1
Order By: Relevance
“…Other functions of smartphones, such as to-do lists could also be useful in reducing forgetfulness [20]. Furthermore, Svoboda and colleagues [18] found using a single case experimental design that smartphone use increased 4 confidence in memory demanding situations, reduced caregiver strain and increased quality of life in one 18 year old with memory impairment [18].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Other functions of smartphones, such as to-do lists could also be useful in reducing forgetfulness [20]. Furthermore, Svoboda and colleagues [18] found using a single case experimental design that smartphone use increased 4 confidence in memory demanding situations, reduced caregiver strain and increased quality of life in one 18 year old with memory impairment [18].…”
Section: Introductionmentioning
confidence: 99%
“…Gillette and DePompei [20] found that students with TBI and intellectual difficulties, aging from six to 20 years, were more often on time and were more independent if they used a PDA or smartphone, compared to using a list or planner. However, this study was undertaken with a small sample of 35 students attending special educational settings, therefore the results may not be generalisable to children in mainstream education [20]. Additionally, this study only assessed the usefulness of the alarm function to prompt on time behaviour.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations